COVID-19 and the public perception of travel insurance. (September 2021) - Tan, David; Caponecchia, Carlo
Highlights: Many travellers have had their insurance claims denied during the COVID-19 crisis. Catastrophic risks are not diversifiable by insurers and excluded in coverage. Travellers will likely revise the perceived value of travel insurance downwards. This will exacerbate the economic fallout via a reverse moral hazard effect. We discuss recommended actions for stakeholders.